Mixed jamming suppression algorithm for phased array radar - Meng Zhang; Xinyu Zhang; Wanjie Song; Wenqing Kong; Zijing Zhang (The Journal of Engineering, 2019)
The most common type of mixed jamming is composed of blanket jamming and deception jamming. In order to effectively detect the target signal in this kind of mixed jamming, this study presents an algorithm based on side-lobe cancellation (SLC) and slope-varying linear frequency modulation signal. The entire anti-jamming process is divided into two steps. SLC is used to suppress blanket jamming first, and then matched filtering is used to suppress deception jamming. The combination of these two algorithms can effectively suppress mixed jamming and accurately detect the target. The simulation analysis shows that this method can effectively detect the target signal in the mixed jamming.